CORRELATION BETWEEN MATERNAL DYSLIPIDEMIA AND PRETERM DELIVERY IN TERTIARY CARE CENTRE- A CLINICAL STUDY. - Dr. R. Nithya; Preethika A; Monisha devi SS; Vatsala Shahi (Student's Journal of Health Research, 2023)
Background:  Pregnancy is the physiological process in a woman's reproductive life. Though all pregnancies carry a risk, almost all pregnancies go uneventfully. In normal pregnancy, as the gestation advances, there is a physiological rise in triglycerides and cholesterol. Hypertriglyceridemia and hypercholesterolemia are markers of preterm labor, as atherosis of uteroplacental spiral arteries can result in preterm labor. Aims & objectives:  To evaluate the correlation of increased levels of fats in uncomplicated gestation with preterm delivery Materials & methods:  An observational study was conducted prospectively in the Department of Obstetrics & Gynaecology in Sree Balaji Medical College & Hospital, Chennai from Jan 2021 to July 2022, which included all Antenatal women between 14 to 32 weeks with no complications and who are planning to deliver in SBMCH. Results:  Out of 290 Pregnant Women, 90.7% delivered at full term, whereas 9.3% had preterm deliveries. 12% had high serum cholesterol levels & 7.5% of them had hypertriglyceridemia. In this study, women who had preterm deliveries had elevated levels of lipids such as LDL and triglycerides, which is statistically significant. Conclusion:  Early births are connected with high neonatal and infant mortality. According to statistical analysis of this study, women with intermediate or higher total, LDL, and triglyceride levels were more likely to deliver before 37 weeks of gestation than those with normal lipid profiles. Pregnancy dyslipidemia was also linked to BMI > 25 kg/m2 and advanced age. Recommendation:  Based on these observations, we could recommend routine lipid profile assessment and management of dyslipidemia during pregnancy and in those planning to conceive, especially in relatively older women and those with obesity.